Tunable blue/yellow emission in high-power white LED devices packaged with Ce:(Y, Gd)AG transparent ceramics. Issue 11 (1st August 2019) - Shao, Cen; Zhang, Le; Zhou, Tianyuan; Gao, Pan; Kang, Jian; Sun, Bingheng; Hou, Chen; Li, Yixin; Yao, Qing; Wu, Jiadonng; Chen, Hao
Abstract: White LEDs have been widely used in various lighting applications. However, applying them to high lumen density systems remains a challenging issue due to the aging of the organic packing materials. In this paper, Ce:(Y, Gd)AG transparent ceramics with different Gd 3+ substitution concentrations were fabricated via solid-state reaction method under different sintering temperatures and used to construct high-power white LED devices to evaluate their optical, luminescence, and thermal properties. The energy band structure of Ce 3+ was effectively tailored by the energy level compressing and orbital hybridisation effects, resulting in the tunability of the blue/yellow emission of the devices and the luminescence redshift of Ce:(Y, Gd)AG ceramics. The transmittance of Ce:(Y, Gd)AG transparent ceramics had almost no impact on the photoluminescence spectra yet exhibited strong dependence on the Gd 3+ substitution concentration. The emitted light of LED devices packaged with the ceramics changed from blue-white to yellow-white while increasing Gd 3+ concentrations from 0.0 to 30.0 at.%. The as-assembled white LED devices exhibited excellent heat dissipation performance, uniform intensity distribution, and strong intensity in the forward direction. The industrialisation of Ce:YAG transparent ceramics-based LED devices can be accelerated especially in high-power lighting.